Anthropological study of body management and health care: Afghan women’s life experience using herbal medicine during childbirth (A Qualitative study in Jalalabad city) - Dadman, Enayatullah; Rasooli , Ajmal (The Indonesian Journal of Social Studies, 2022)
Pregnancy and childbirth have been an integral part of human existence for thousands of years, but unfortunately, the experience has not been easy for all women. Many medicines are available, but the potential for harm is not negligible, as illustrated in thalidomide in 1958. Therefore, many mega medicines are not recommended for use during pregnancy because they have known or suspicious problems or are not sufficient to say that they are safe. In this respect, Chinese herbs are gaining popularity in both developing and developed countries due to their natural origin and relatively safeness with few side effects. This article gives an overview of some of these plants used around Jalalabad city during pregnancy, childbirth, and postnatal care. We examined about 20 species of plants belonging to different families, the most common of which are Asparagus racemosus (Liliaceae), Apium graveolens (Umbelliferae), RheumOfficinalee Polygonaceaee), Veratrum nigrum (Melanthiaceae). Met. From the available studies, it can be concluded that herbal medicines can be used during pregnancy, childbirth, and postnatal care after proper verification of the plant.